Weirdo19ES is a novel singleton mycobacteriophage that selects for glycolipid deficient phage-resistant M. Smegmatis mutants - Suárez, Cristian Alejandro (2020)
The sequencing and bioinformatics analysis of bacteriophages infecting mycobacteria has yielded a large amount of information on their evolution, including that on their environmental propagation on other genera such as Gordonia, closely related to Mycobacterium. However, little is known on mycobacteriophages cell biology such as the nature of their receptor (s) or their replication cycle. As part of our on-going screening for novel mycobacteriophages, we herein report the isolation and genome bioinformatics analysis of Weirdo19ES, a singleton Siphoviridae temperate mycobacteriophage with a 70.19% GC content. Nucleotide and protein sequence comparison to actinobacteriophage databases revealed that Weirdo19ES shows low homology to Gordonia phage Ruthy and mycobacteriophages falling in clusters Q and G and to singleton DS6A.Weirdo19ES also displays uncommon features such as a very short Lysin A gene (with only one enzymatic domain) and two putative HNH endonucleases. Mycobacterium smegmatis mutants resistant to Weirdo19ES are cross- resistant to I3. In agreement with that phenotype, analysis of cell envelope of those mutants showed that Weirdo19ES shares receptors with the transducing mycobacteriophage I3.This singleton mycobacteriophage adds up to the uncommonness of local mycobacteriophages previously isolated by our group and helps understanding the nature of mycobacteriophage receptors.